Effectiveness of hospital payment reforms in low- and middle-income countries: a systematic review. Issue 8 (6th May 2021) - Ghazaryan, Emma; Delarmente, Benjo A; Garber, Kent; Gross, Margaret; Sriudomporn, Salin; Rao, Krishna D
Abstract: Payment mechanisms have attracted substantial research interest because of their consequent effect on care outcomes, including treatment costs, admission and readmission rates and patient satisfaction. Those mechanisms create the incentive environment within which health workers operate and can influence provider behaviour in ways that can facilitate achievement of national health policy goals. This systematic review aims to understand the effects of changes in hospital payment mechanisms introduced in low- and middle-income countries (LMICs) on hospital- and patient-level outcomes. A standardised search of seven databases and a manual search of the grey literature and reference lists of existing reviews were performed to identify relevant articles published between January 2000 and July 2019. We included original studies focused on hospital payment reforms and their effect on hospital and patient outcomes in LMICs. Narrative descriptions or studies focusing only on provider payments or primary care settings were excluded. The authors used the Risk of Bias in Non-Randomized Studies of Interventions tool to assess the risk of bias and quality. Results were synthesized in a narrative description due to methodological heterogeneity. A total of 24 articles from seven middle-income countries were included, the majority of which are from Asia. In most cases, hospital payment reforms included shifts from passive (fee-for-service) to active payment models—the most common being diagnosis-related group payments, capitation and global budget. In general, hospital payment reforms were associated with decreases in hospital expenditures, out-of-pocket payments, length of hospital stay and readmission rates. The majority of the articles scored low on quality due to weak study design. A shift from passive to active hospital payment methods in LMICs has been associated with lower hospital and patient costs as well as increased efficiency without any apparent compromise on quality. However, there is an important need for high-quality studies in this area.